2007
DOI: 10.1128/aem.01744-06
|View full text |Cite
|
Sign up to set email alerts
|

Historical and Contemporary NaCl Concentrations Affect the Duration and Distribution of Lag Times from Individual Spores of Nonproteolytic Clostridium botulinum

Abstract: In this study we determined the effect of NaCl concentration during sporulation (0 or 3.0% [wt/vol] added NaCl) and subsequent growth (0 or 2.0% [wt/vol] added NaCl) on the distributions of times associated with various stages of the lag phase of individual spores of nonproteolytic Clostridium botulinum strain Eklund 17B. The effects of NaCl on the probability of germination and the probability of subsequent growth were also determined. Spore populations exhibited considerable heterogeneity at all stages of la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
21
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 27 publications
4
21
0
Order By: Relevance
“…The asymmetric shape of the germination distribution curves, with a majority of spores germinating within a short time interval followed by a long tail of late-germinating spores, is similar to that reported in previous germination-only studies of individual spores of bacillus or clostridia (4,5,6,7,11,21,22,23). Billon et al examined the effect of incubation temperature on germination times for individual spores of proteolytic C. botulinum 62A (4).…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…The asymmetric shape of the germination distribution curves, with a majority of spores germinating within a short time interval followed by a long tail of late-germinating spores, is similar to that reported in previous germination-only studies of individual spores of bacillus or clostridia (4,5,6,7,11,21,22,23). Billon et al examined the effect of incubation temperature on germination times for individual spores of proteolytic C. botulinum 62A (4).…”
Section: Discussionmentioning
confidence: 60%
“…Germination differs from later growth events since it is a series of degradative reactions using preformed enzymes, whereas subsequent growth stages require macromolecular synthesis (13). Previous studies of lag times have shown individual spores are highly heterogeneous with all stages of lag contributing to variability (21,23). Changes in environmental conditions, such as growth temperature, are likely to affect all stages of lag but may not necessarily affect all stages to the same extent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed heterogeneity is the sum of heterogeneity during germination, the first doubling phases, and further outgrowth and is likely to result from multiple sources (6,15). For C. botulinum, it has been shown that the first spore that germinated was not the first to develop into a vegetative cell, also under stress conditions, highlighting the lack of correlation between germination and outgrowth times (12)(13)(14)19). The most important source of variability in outgrowth might depend on the relative magnitude of the contributions of the different phases in outgrowth.…”
mentioning
confidence: 99%
“…CO 2 concentration affected spore coat protein gene expression, especially that of CBO0114 (similar to Bacillus subtilis YtaA and Clostridium tetani spore coat protein (16). This marked effect may influence properties of the spore coat and thereby spore resistance and the time to emergence for germinated spores (31,32,35). Spore germinant receptor proteins are usually encoded by tricistronic operons, of which there are three in the ATCC 3502 genome (28).…”
Section: Resultsmentioning
confidence: 99%